Proceedings of the 9th International Conference on Ubiquitous Information Management and Communication 2015
DOI: 10.1145/2701126.2701153
|View full text |Cite
|
Sign up to set email alerts
|

Cluster based emergency message dissemination scheme for vehicular ad hoc networks

Abstract: Wireless and mobile communications has experienced an unprecedented rapid growth during the last decade. Vehicular Ad Hoc Networks (VANETs) are a completely wirelessly connected through the nodes, which usually has dynamic topologies. VANETs can be employed in many applications such as traffic control, safety related message dissemination, and entertainment infotainment. Broadcast storm problem is one of the hot issues in VANETs as it lacks of central management. Many methods are proposed to solve this problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The basic concept of MPECS was to split the whole region into separate areas by the Voronoi graph; in order to enable each vehicle to estimate its lifetime and cost of becoming the cluster head in its current location. The proposed technique has shown evidence of significant MPECS capabilities enhance clustering design reliability with reduced overhead, finally, in [54]. This study suggested a modern scheme of data distribution focused on clustering and CBD.…”
Section: Cluster-based Data Disseminationmentioning
confidence: 78%
See 1 more Smart Citation
“…The basic concept of MPECS was to split the whole region into separate areas by the Voronoi graph; in order to enable each vehicle to estimate its lifetime and cost of becoming the cluster head in its current location. The proposed technique has shown evidence of significant MPECS capabilities enhance clustering design reliability with reduced overhead, finally, in [54]. This study suggested a modern scheme of data distribution focused on clustering and CBD.…”
Section: Cluster-based Data Disseminationmentioning
confidence: 78%
“…To avoid unwanted propagation, which can also trigger the issue of the transmitted hurricane, the time barrier methods are modified in order to resolve the problem. While in [54], a modern, efficient clustering simulation versatility (MPECS) system was proposed. The basic concept of MPECS was to split the whole region into separate areas by the Voronoi graph; in order to enable each vehicle to estimate its lifetime and cost of becoming the cluster head in its current location.…”
Section: Cluster-based Data Disseminationmentioning
confidence: 99%
“…In this section, we evaluated the proposed mechanism using OMNeT++ [43], simulation of urban mobility (SUMO) [27] and Veins [40] platform. The proposed algorithm is compared to clustering based probabilistic broadcasting (CPB) [30], cluster-based EM dissemination proposed by Jin et al (termed as Jin Model) [23] and simple flooding. In CPB, data is disseminated using probabilistic forwarding, and the CH is responsible for dissemination of messages.…”
Section: Performance Evaluationsmentioning
confidence: 99%
“…Therefore, how to select an appropriate area to achieve effective data dissemination is more important. Although, there are many researches about the issue [1] [2] [3] and a lot of novel schemes are proposed [4] [5], they usually consider the location of event as the dissemination area. This leads to more control packets and delay time when vehicles do not know the dissemination area or need multiple event informations at the same time.…”
Section: Extended Abstractmentioning
confidence: 99%